PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA - Misbahul Khoer (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The aim of this study is to determine the student creative thinking ability after applyingcooperative learning Numbered Head Together (NHT) model. The research method used iseksperiment method with design of nonequivalent pretest-posttest control group design. Thepopulation in this study were all students of class VII junior high school in Kuningan in the theacademic year 2014/2015. Through purposive sampling technique, 2 classes were selected assamples where the class VIIA as the control class and VIIC as experimental class with a totalsample of 56 students. Data collection tehniques were obtained through creative thinking abilitytest and data analysis tehniques included normality test, homogenity test, and t test. The resultsshowed that student creative thinking ability after applying cooperative learning Numbered HeadTogether (NHT) model on Social subject can provide maximum results in students learningoutcomes.Kata-kata kunci : Berpikir Kreatif, Model Pembelajaran Kooperatif, Numbered Head Together.